The visual interface of “comprehensive design” - Kostesic, Iva; Vukić, Fedja (InfoDesign, 2019)
The purpose of this article is to gather and analyse the visual appearance and interface of “comprehensive design” within different historic, social and cultural contexts. As elaborated by R. B. Fuller in 1949, the “comprehensive designer” is "an emerging synthesis of artist, inventor, mechanic, objective economist and evolutionary strategist", who is to synthesize the knowledge produced by various fields of science and tries to bring balance to the world. The notion of comprehensive design can be seen as a way of designing in regards to and across both small and large scale design activities that perceive the world as an interconnected system. As to answer how this notion was visualized, the article will analyse the interfaces of “comprehensive design” including May’s New Frankfurt, Fuller’s “World Game”, Bonsiepe’s Cybersyn project and Archigram’s projects which seem to have high relevance in the contemporary efforts in designing a new type of sustainable city.